SISTEM MANAJEMEN REPARASI KOMPUTER PADA CV NEXTGEN PC BERBASIS PAYMENT GATEWAY - Frans Rivaldi Pinem; Ardi Taryanto (LPPM Politeknik Pajajaran ICB Bandung, 2025)
The rapid development of information technology has influenced various business sectors, including computer repair services. CV NextGen PC still encounters problems such as inefficiency in handling repair requests, providing cost quotations, tracking repair progress, and managing transparent payments. This study proposes the development of a Computer Repair Management System at CV NextGen PC using a web-based platform integrated with a payment gateway. The system was developed using the Waterfall model and modeled with the Unified Modeling Language (UML) to ensure a structured design process. The implementation produced a web-based application accessible through browsers and integrated with PayPal for online transactions. System functionality was validated using Blackbox Testing to ensure that repair requests, quotation management, repair status tracking, delivery management, and payment processes operate correctly. The results indicate that the system improves service efficiency, minimizes administrative errors, and enhances customer satisfaction through real-time tracking and transparent digital transactions. This study concludes that the system provides an effective solution for digitalizing repair services at CV NextGen PC and can be further enhanced through mobile integration for wider accessibility. Keywords: Blackbox Testing, Computer Repair Service, Payment Gateway, Web-based System